Jammed Emulsions with Adhesive Pea Protein Particles for Elastoplastic Edible 3D Printed Materials. (11th July 2021) - Sridharan, Simha; Meinders, Marcel B. J.; Sagis, Leonard M.; Bitter, Johannes H.; Nikiforidis, Constantinos V.
Abstract: 3D printed materials are of great relevance to produce medicinal scaffolds and specialized foods. An approach to forming 3D printable materials is to use jammed oil droplets. Jammed oil droplets are highly viscous and can be extruded through the nozzle of a 3D printer, while after chemical cross‐linking they acquire a self‐standing ability. However, the molecules currently used to stabilize and cross‐link the oil droplets have questionable biocompatibility. Therefore, this study aims to produce a 3D printable jammed emulsion using pea proteins. This jammed oil‐in‐water emulsion is remarkably stable and viscoelastic enough to be extruded through the printer nozzle. Adhesive pea protein particles formed by pH adjustment act as physical cross‐links between the oil droplets, forming a scaffold with elastoplastic rheological properties that flows above critical stress while, without any additional treatment, exhibits the required self‐standing properties for 3D printing. By understanding the properties of pea proteins and their behavior in bulk and on interfaces, pea protein‐based 3D printable material is created for the first time. Abstract : 3D printing of edible emulsions can be used to create specialized foods and to deliver bioactive molecules. Usually, particles such as cellulose are used to create such materials, which require cross‐linking to stabilize 3D printed structures. However, this study shows 3D printable material can be created using jammed emulsions with pea proteins and simple pH adjustments without requiring additional treatments.